Entrepreneurial Mindset, Emotional Intelligence, Grit, Entrepreneurial Self-Efficacy dan Entrepreneurial Intention Generasi Z - Tanoto, Sherly Rosalina; Indrastata, Rahadwitya Dian (Psychopreneur Journal, 2025)
Generation Z, comprising the largest population group in Indonesia, faces significant unemployment challenges. This article explores the factors influencing entrepreneurial intention among Indonesian students to tackle unemployment and enhance the economy. The research aims to examine the roles of entrepreneurial mindset, emotional intelligence, and grit in shaping entrepreneurial intention through entrepreneurial self-efficacy. The study employs a quantitative research method, utilizing non-probability sampling techniques, collecting data from 269 students in semester 5 and above across Indonesia. Research findings indicate that entrepreneurial mindset positively impacts entrepreneurial intention, while emotional intelligence and grit do not significantly affect it. Additionally, entrepreneurial mindset, emotional intelligence, and grit are correlated with entrepreneurial self-efficacy. Entrepreneurial self-efficacy serves as a mediating factor between entrepreneurial mindset, emotional intelligence, grit, and entrepreneurial intention. These results contribute significantly to Indonesia's efforts in optimizing Generation Z's entrepreneurial potential to address unemployment challenges and strengthen the economy.